Mediastinoscopy. Analysis of 107 cases - Aquino, Alfredo A.; Fernández Roth, César A.; Cuper, Lucía S.; Orban, Raúl D.; Torres, Ricardo A. (Revista Argentina de Cirugía, 2021)
Background: the current management of lung cancer should be based on the TNM staging, in accordance with the International Association for the study of Lung Cancer (IASLC). CT and PET scan help to rule out involvement of Mediastinal nodes, while mediastinoscopy may confirm involvement the histology of allow for the diagnosis of other diseases. Objectives: to assess the results of mediastinoscopy in the diagnosis and staging of diseases with me- diastinal lymph node compromise. Material and methods: we studied 107 mediastinoscopies and videomediastinoscopy carried out between March 2012 and March 2014. We included patients with lung cancer (CP) suspected or known and those with diseases that present mediastinal lymph node compromise. The indications were diagnosis and staging of CP in 73 cases, staging of CP 13, and diagnosis of mediastinal adenopathy in 21 patients. We calculated the sensitivity, specificity, the positive predictive value (PPV), the negative predictive value (NPV) and the diagnostic yield. Results: of 107 cases, 71 were male (66.4%). In 56 cases, we had a histological diagnosis of certainty. A sensitivity of 93.3 %, specificity 100 %, positive predictive value of 100 %, negative predictive value of 90 % and a diagnostic accuracy of 95.8 % was obtained. The morbidity was three cases (3.1%). Conclusions: the mediastinoscopy has proven to be a safe, very specific and sensitive technique in the assessment of lymph node involvement with a low rate of morbidity and mortality